New Brunswick - Canada. Surveys and Mapping Branch (Department of Mines and Technical Surveys Canada, 1962)
This is a general map of New Brunswick in 1962 showing roads, railways, trails, provincial parks, First Nations reserves, cities and towns. "MCR 29" Material digitized as part of an Academic Innovation Fund (AIF), awarded in 2018. For more information see: http://avptl.info.yorku.ca/academic-innovation-fund/ . Scale 1:500,000, or 7.89 miles to 1 inch. Relief shown pictorially and by spot heights. Transverse Mercator projection, central meridian 66°30'. Shows roads, railways, trails, provincial parks, First Nations reserves, cities and towns.